Analysis of the Potential and Implementation of Risk Management in Sharia Financing for Shallot Farmers in Brebes Regency - M Fauzan Ali Muzaki; Alvin Yahya (Mutanaqishah: Journal of Islamic Banking, 2026)
Purpose – This study aims to analyze the potential of Islamic financing in the shallot farming sector in Brebes Regency, including the financing mechanisms and analysis applied, as well as the implementation of risk management by Islamic banks in distributing financing to shallot farmers. Methodology – This study uses a qualitative method with a descriptive-exploratory approach to understand the phenomenon as it naturally emerges from informants. Data collection was conducted through semi-structured interviews with relevant parties, including the head of the shallot farmer group in Rengaspendawa village, the marketing department of Bank Syariah Indonesia KCP A Yani 1 Brebes, and the Mantri Tani (farmer advisor) at the Rengaspendawa village, Larangan Subdistrict Agricultural Extension Center. Findings – This study shows that sharia financing has significant potential to support shallot farming in Brebes Regency due to the high capital requirements and the business feasibility. The financing mechanism applies the 5C principle with an emphasis on character and cash flow analysis, while risk management is carried out preventively, mitigatively, and through continuous monitoring. This approach is effective in minimizing financing risk and supporting the sustainability of farmers' businesses. Implications– The results of this study emphasize the importance of developing Islamic financing schemes that are adaptive to seasonal patterns and agricultural risks in Brebes Regency, through strengthening risk management and collaboration between Islamic banks, farmers, and local governments to support sustainable access to capital. Originality– This study contributes to the literature by empirically analyzing the integration of sharia financing and risk management in the shallot farming sector in Brebes Regency, emphasizing the seasonal and high-risk characteristics of farming businesses.